Media Pembelajaran Video Animasi Organ Tubuh Manusia - Arif Rinaldi Dikananda; Iin Iin; Saeful Anwar; Raditya Danar Dana; Kanda Muhamad Ishak (Jurnal Accounting Information System (AIMS), 2021)
Interactive video is a technology for sending electronic signals from a moving image that can describe information which in the process occurs 2-way communication between multimedia and users. This research started from the problems encountered, namely the number of elementary school students who still do not know and do not understand the human organs. The method used is the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The use of interactive video based on 2D animation is expected to attract students so they don't get bored while learning using video. The applications used to create these interactive learning videos are Corel Draw X7 for creating digital sketches and Adobe After Effects for editing digital sketches into a video. The results in this study are interactive learning videos about human organs. Learning videos can be used by students so that they can increase student interest in learning because there are 2D animations and interactions with users and can be used anytime and anywhere. So it can be concluded that this learning video received a very good response from students because it is effectively used when studying at school and at home. Respondents were taken as many as 50 students. The results of this study obtained an increase in student understanding from 40% of students or as many as 20 students to 76% or as many as 38 students. There was an increase of 36%.